Analisis Implementasi Metode Pembelajaran Field Trip Terhadap Hasil Belajar Siswa Sekolah Dasar - Muadi, Faisal; Kasmini, Lili; Sari, Siti Mayang (Indo-MathEdu Intellectuals Journal, 2023)
Learning can be obtained by students not only within the school environment, but outside the school environment students can explore knowledge related to the material in the classroom through the field trip learning method. This study aims to determine the application of field trip learning methods to the learning outcomes of students in Elementary School (SD). This research uses a type of qualitative descriptive research with literature studies from relevant research. Data is obtained from various sources including published articles, books, and other relevant literature. The results of this research show that the field trip learning method is a learning method that can direct students to study somewhere directly according to the material they are studying. The field trip learning method can have a positive impact on student learning outcomes. So it can be concluded that in learning teachers can use a variety of learning methods that are adapted to the material, one of which is using the field trip method with their students